Strategi Multidimensional dalam Penanganan dan Pencegahan Stunting melalui Program Kesehatan, Lingkungan, dan Hukum di Kelurahan Kaligangsa - Susilowati, Nurdian; Saputri, Atha Difa; Devana Nazwa, Syarla; Najkhan, Azka (Universitas Negeri Semarang, 2025)
This study aims to address and prevent stunting in Kaligangsa Village through a multidimensional approach. The methods used include data collection, home visits, education, and provision of nutritious food. Initial data showed that there were 38 children with stunting out of a total of 191 toddlers. Educational activities include the importance of environmental cleanliness, provision of nutritious food, and health rights for women. The